2018
DOI: 10.1002/ceat.201800290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Design Parameters on Biomass Separation in Mini‐hydrocyclones

Abstract: Small hydrocyclones are an attractive technology for biomass separation from fermentation processes. The interactive effect of design parameters on the performance of mini‐hydrocyclones is, however, not fully explored and studies are often limited by the challenges in manufacturing such small units. Here, 10‐mm mini‐hydrocyclones are produced by 3D printing and the impact of spigot diameter, vortex finder diameter and height on separation performance is studied. A central composite rotatable design was adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…These parameters were changed based on previous papers to improve the separation performance. For instance, it was found that expanding the overflow diameter has a positive impact on the separation process [11,38], so it was increased to 5 mm in the current work. However, the separation performance was found not to be influenced by the height of the vortex finder [38], so it was not changed.…”
Section: Geometry Of the Hydrocyclonesmentioning
confidence: 82%
See 1 more Smart Citation
“…These parameters were changed based on previous papers to improve the separation performance. For instance, it was found that expanding the overflow diameter has a positive impact on the separation process [11,38], so it was increased to 5 mm in the current work. However, the separation performance was found not to be influenced by the height of the vortex finder [38], so it was not changed.…”
Section: Geometry Of the Hydrocyclonesmentioning
confidence: 82%
“…The total experimental concentration ratio was obtained as 1.2 for MC‐3at 120 mL s −1 inlet flow rate and 0.5 wt % feed concentration which is higher than reported by Pinto et al (1.11) 47 with the same particle size. Overall, there is a trade‐off between amount of solid recovery from underflow and concentration ratio although both of them are the separation performance 38. In fact, the high solid recovery might not mean the better separation performance because it is possible that the most of the inlet volume flow rate exits from the underflow for the sake of a large underflow diameter.…”
Section: Resultsmentioning
confidence: 99%
“…The operational success of a hydrocyclone depends on the relationship between its main dimensions. Consequently, it is possible to manipulate or optimize the geometric variables of this device in order to meet the demands of a specific application. In addition, its performance can also be improved by modifying its construction, creating the so-called nonconventional hydrocyclones. These new devices may have a parabolic shape instead of conical, the structure of their vortex finder modified, a solid rod inserted along their vertical axis, , and the number of feeds or design of the feed ducts changed. …”
Section: Introductionmentioning
confidence: 99%
“…Experimental research on mini-hydrocyclone design parameters, such as spigot and vortex finder, has often been limited to designs that are commercially available. More recently, this drawback has been overcome by the application of 3D printing technology as a tool for manufacturing mini-hydrocyclones [11,12,13].…”
Section: Introductionmentioning
confidence: 99%